(untitled) (Journal of Comparative & International Higher Education, 2024)
Micro-level internationalization offers possibilities to explore different human experiences in international higher education. This is especially crucial given well-reported issues of racism, micro-aggression, and underrepresentation of racially minoritized international academic staff, whose voices remain mostly invisible in internationalization discourses. Previous research connects these issues to the continuing legacy of colonial logic, that privileges hegemonic Western-centric knowledge systems. In this paper, centrality is proposed as a conceptual framework that offers a direct response to the question of epistemicide which Santos (2014) explains as the exclusion of the knowledges of racially marginalized persons [in or with origins] from the Global South. It draws attention to how epistemicide and historicide (erasure of cultural history) impinge their agentic capabilities, drawing on their lived experiences and cognitive epistemological and ontological frames of knowing and being. Centrality, therefore, reiterates the need to center marginalized voices as legitimate and knowledgeable contributors to conversations and research on decolonizing internationalization, drawing on their knowledge, capabilities, and lived experience. This calls on Global North allies to not only articulate their positionality, acknowledging the inequities inherent in the hegemonic Western-centric epistemology paradigm but to contribute to dismantling persisting structural coloniality and embedded hierarchies in teaching, research, and international partnerships. Centrality thus offers a framework for: i) dismantling the persisting pernicious legacy of colonialization by working collaboratively to undo the epistemic hegemony that perpetuates the universality of Eurocentric knowledge and subalternity of the Global South, and ii) advancing access to ecologies of knowledge that affirms rather than disparages our shared humanity.